IMPLEMENTASI NILAI KEWAJIBAN PEMIMPIN DALAM ISLAM PADA KEBIJAKAN PEMERINTAHAN DESA BERDASARKAN UU NO. 6 TAHUN 2014 - Ghazyan Hidzyam Haqqani (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
Village governments play a central role in Indonesia's governance structure as public service providers at the local level. This research aims to analyze the implementation of Islamic values of leader obligations, such as trustworthiness, justice, and deliberation, in village governance policies based on Law No. 6/2014 on Villages. Using a normative juridical method with statutory, conceptual, and comparative approaches, this research evaluates the implementation of Islamic values through document and literature studies. The results show that although Islamic leadership principles are reflected in the duties of the village head, such as fair management of village funds and community empowerment, implementation faces challenges, including limited resources, diverse understanding, and integrity issues. The study also identified strategic solutions, such as continuous training, strengthening supervision, and increasing community participation. In conclusion, Islamic leadership values have strong relevance in village governance policies and can improve the quality of village governance if optimally implemented. This research contributes to the understanding of the integration of Islamic values in the context of modern governance and recommends more in-depth follow-up studies on specific cases to enrich the literature in this field.